Electroactive microorganisms in coffee processing wastewater (iron redox processes) (UNED Research Journal, 2023)
Introduction: Wastewater is often a good source for electrogenic bacteria, which are essential for Microbial Fuel Cells (MFCs). The electrons they release while metabolizing organic matter is evidence of their electrogenic capacity. Objective: To evaluate the iron-reducing capacity of bacteria isolated from coffee wastewater. Methods: We isolated morphologically distinct facultative bacteria from the anode electrode of MFCs, with coffee mill wastewater as our substrate. We did a preliminary identification with the Biolog GEN III system (Biolog Inc. Hayward, CA, USA). To assess the conversion of iron (III) to iron (II) by the isolated bacteria, we tested iron (III) citrate, iron (III) chloride, and iron (III) oxide. For comparison, we used S. oneidensis as a positive control in our experiments. Results: We identified eight bacterial isolates with a predominance of non-sporulated Gram positive bacilli morphology. They have reductive activity of iron compounds, giving the best conversion percentages from  a  for iron oxide (III). The isolate coinciding with the genus Citrobacter (SB), the only Gram negative bacillus, obtained iron conversion percentages higher than 1,0% in the three iron compounds (maximum: 4,3%). Conclusion: In the residual water from the coffee process, there are bacteria with electrogenic capability that could be used in Microbial Fuel Cells.
Keywords: microbial fuel cell; electrogenic; bacteria; wastewater; iron reduction